2013
DOI: 10.1037/a0031356
|View full text |Cite
|
Sign up to set email alerts
|

Adults’ earliest memories as a function of age, gender, and education in a large stratified sample.

Abstract: Childhood amnesia (i.e., a marked paucity of memories from the first 3-4 years of life) has often been examined by asking people for their earliest memory. Such studies have generally been conducted with college students, and thus been unable to examine possible effects of education and current age. We here report the first study on adults' earliest memories based on a large, stratified sample covering the adult life span from age 20 to 70 (n = 1,043). Because of the nature and size of our sample we have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(62 citation statements)
references
References 45 publications
10
52
0
Order By: Relevance
“…For example, in the previous study on adults' earliest memories, it was found that adults' earliest memories can be dated back to the time when the respondents were between 3 and 4 years of age (Jack & Hayne, 2007). Regarding gender differences as well results go along with the earlier studies (Kingo et al, 2013).…”
Section: Discussionsupporting
confidence: 75%
“…For example, in the previous study on adults' earliest memories, it was found that adults' earliest memories can be dated back to the time when the respondents were between 3 and 4 years of age (Jack & Hayne, 2007). Regarding gender differences as well results go along with the earlier studies (Kingo et al, 2013).…”
Section: Discussionsupporting
confidence: 75%
“…However, this pattern was general to almost all characteristics measured here: Older adults rated events more highly than did younger adults. Such results have been found previously, but have not been fully explained or understood (Kingo, Berntsen & Krøjgaard, 2013;, as Rubin and Schulkind (1997) stated, "Not much can be made of it except that it warrants further study (p. 532)."…”
Section: Discussionmentioning
confidence: 61%
“…In many studies of the recall of earliest memories the first memory is found to date to the 3rd year of life, typically about 3 years 4 months (Hayne, 2004;Kingo, Berntsen, & Krøjgaard, 2013a;Pillemer & White, 1989;Rubin, 2000;Wang, Conway, & Hou, 2004). However, also in many studies, there are always a few respondents who date their earliest memory to 2 years of age and below (Hayne, 2004;Wells, Morrison & Conway, 2013; see too Kingo, Berntsen, & Krøjgaard, 2013b).…”
mentioning
confidence: 99%